الدفاع الشرعي بين الشرعية والانتهاك لقواعد القانون الدولي - لونيسي, علي; خليفي, سمير (جامعة الوادي University of Eloued, 2019)
أعلن العديد من مسؤولي حكومة الولايات المتحدة الأمريكية غداة هجمات 11 سبتمبر 2001 عن حق دولتهم في الدفاع الشرعي عن نفسها، ضد هذه الهجمات، استناداً لنص المادة (51) من ميثاق منظمة الأمم المتحدة، وما زاد من الأمر تعقيداً، وأدى إلى الكثير من الخلاف والجدل بين المهتمين بدراسة القانون الدولي هو صدور القرار رقم (1368) عن مجلس الأمن الدَّولي في اليوم الموالي لتلك الهجمات، والذي أكد على الحق الطبيعي للدول في الدفاع عن نفسها فرادى أو جماعات طبقاً لنص المادة (51) من ميثاق منظمة الأمم المتحدة، وذلك على الرغم من عدم إشارته إلى ان هذه الهجمات تشكل عدواناً أو هجوماً مسلحاً ضد الولايات المتحدة الأمريكية، بل اعتبرها كغيرها من الهجمات الإرهابية والتي تشكل تهديداً للسلم والأمن الدوليين. Many officials of the United States of America declared in the wake of the September 11, 2001 attacks, the right of their state to defend itself against these attacks on the basis of Article (51) of the Charter of the United Nations. The resolution (1368) of the United Nations Security Council on the day following the attacks affirmed the inherent right of States to defend themselves individually or in groups in accordance with Article (51) of the Charter of the United Nations, which complicated the matter and led to much controversy among those interested in studying International law, although it did not mention that these Attacks constitute an aggression or an armed attack against the United States, but as other terrorist attacks, which pose a threat to international peace and security.
غزو أفغانستان من قبل الولايات المتحدة الأمريكية في 04/10/2001-نموذجا
Keywords: هجمات 11 سبتمبر 2001، القرار رقم (1368)، المادة (51) من الميثاق، الهجمات الإرهابية، تشكل عدواناً، الدفاع عن نفسها فرادى أو جماعات; September 11, 2001 attacks - Resolution (1368), Article (51) of the Charter - Terrorist attacks - Aggression - Individual or collective self-defense.